Exercises Pursued by Older Adults with Osteoarthritis and Their Structural Impacts are Hard to Uncover; a Scoping Review of Selected 1970-2024 Studies - Marks Ray (Journal of Aging Research And Healthcare, 2024)
Persons with osteoarthritis often have signs of reduced muscle strength. Some studies suggest that this strength could be improved with exercise. However, does this form of therapy improve the disease status as assessed by improvements in cartilage viability, a hallmark of the disease? This brief describes the possible usage of exercises in general, plus those known to improve strength and function, and reduce pain and whether structural impacts that favor or impede disease regression have been observed in this context among the older osteoarthritis adult population. Since exercise may also do harm, rather than good in osteoarthritis management if excessive, contra indicated, or suboptimal, what is the consensus in this regard in 2024?
Keywords: Articular Cartilage